Implementasi Projek Penguatan Profil Pelajar Pancasila P5 Dalam Pembentukan Karakter Peserta Didik SMP Negeri 11 Pontianak (CIVICS: Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2025)
This research aims to find out about the implementation of strengthening projectsPancasila student profile in shaping student character through three themes The project's theme is sustainable lifestyle, building body and soul, and diversity in diversity. This research using a qualitative approach with descriptive methods. Data obtained from interviews with the Principal, Chief Project Coordinator, Team Facilitators and Learners. Data was obtained through interviews and observations and documentation. The research results show that 1)implementation flow P5 at SMP Negeri 11 Pontianak includes planning, implementation and evaluation stages 2) Theme build the soul and body in the dimension of faith and devotion to God Almighty and having good morals noble achieved through social service to nursing homes. Unity in diversity theme ika in the dimension of global diversity achieved through 3 ethnic dances. The theme of a sustainable lifestyle in a creative dimension is achieved through management of used goods 3) obstacles in the P5 project, namely lack of teacher understanding of the P5 project module,Lack of teaching staff, infrastructure limited. Alternative solution, the teacher arranges a module according to personal understanding regarding the project, accept students intern to help with P5 activities. move project activities to the front yard of the school